Polyaniline/Ti3C2 MXene Composites with Artificial 3D Biomimetic Surface Structure of Natural Macaw Feather Applied for Anticorrosion Coatings - Chen-Cheng Chien; Yu-Hsuan Liu; Kun-Hao Luo; Ting-Yun Liu; Yi-Ting Kao; Shih-Harn Yang; Jui-Ming Yeh (Biomimetics, 2025)
In this paper, a series of polyaniline (PANI)/Ti3C2 MXene composites (PMCs) with a biomimetic structure were prepared and employed as an anticorrosion coating application. First, the PANI was synthesized by oxidative polymerization with ammonium persulfate as the oxidant. Then, 2D Ti3C2 MXene nanosheets were prepared by treating the Ti3AlC2 using the optimized minimally intensive layer delamination (MILD) method, followed by characterization via XRD and SEM. Subsequently, the PMC was prepared by the oxidative polymerization of aniline monomers in the presence of Ti3C2 MXene nanosheets, followed by characterization via FTIR, XRD, SEM, TEM, CV, and UV–Visible. Eventually, the PMC coatings with the artificial biomimetic surface structure of a macaw feather were prepared by the nano-casting technique. The corrosion resistance of the PMC coatings, evaluated via Tafel polarization and Nyquist impedance measurements, shows that increasing the MXene loading up to 5 wt % shifts the corrosion potential (Ecorr) on steel from −588 mV to −356 mV vs. SCE, reduces the corrosion current density (Icorr) from 1.09 µA/cm2 to 0.035 µA/cm2, and raises the impedance modulus at 0.01 Hz from 67 kΩ to 3794 kΩ. When structured with the hierarchical feather topography, the PMC coating (Bio-PA-MX-5) further advances the Ecorr to +103.6 mV, lowers the Icorr to 7.22 × 10−4 µA/cm2, and boosts the impedance to 96,875 kΩ. Compared to neat coatings without biomimetic structuring, those with engineered biomimetic surfaces showed significantly improved corrosion protection performance. These enhancements arise from three synergistic mechanisms: (i) polyaniline’s redox catalysis accelerates the formation of a dense passive oxide layer; (ii) MXene nanosheets create a tortuous gas barrier that cuts the oxygen permeability from 11.3 Barrer to 0.9 Barrer; and (iii) the biomimetic surface traps air pockets, raising the water contact angle from 87° to 135°. This integrated approach delivers one of the highest combined corrosion potentials and impedance values reported for thin-film coatings, pointing to a general strategy for durable steel protection.